Research on Water Quality Improvement Method Based on Slowly-Stored and Quickly-Released System in Xi'an Moat - SUN Chao; HAN Weigang; NONG Xiaoying; WANG Hui; WANG Wenyu; GAO Zehai (Renmin Zhujiang)
The slowly-stored and quickly-released system was studied to explore the method of optimizing the hydrodynamic force of rivers in arid regions and reveal its effect on water quality.The south-west tributary of Xi'an moat was defined as the study area.A hydrodynamic force-water quality coupling model of the moat was built based on the collected data of current water quality and hydrodynamic force by using MIKE21.In the coupling model,the impounding gate was designed based on the dam body of the moat to simulate the scouring and silting capacity of the lower reaches caused by rapid discharge from the upper reaches of the channel.The influence law of rapid discharge at different water levels and water quality conditions on hydrodynamics and water quality of the moat was studied.The numerical simulation results from MIKE21 show that water level has a significant influence on the hydrodynamic force,and water quality has a significant influence on the pollutant concentration.The simulation results of the hydrodynamic force-water quality coupling model of the moat show that the working condition with a 1-meter water level and class Ⅲ inlet water quality can greatly improve the water quality and hydrodynamic force of Xi'an moat.By using the water reaching the standard of the class Ⅲ inlet water quality as the supply source,the water quality of Xi'an moat can be effectively improved by enhancing the hydrodynamic force of the moat.